Antimicrobial Activity of some Tropical Fruit Wastes (Guava, Starfruit, Banana, Papaya, Passionfruit, Langsat, Duku, Rambutan and Rambai) - Mohamed, Suhaila; Hassan, Zahariah; Abd Hamid, Norhashimah (Universiti Putra Malaysia Press, 1994)
Extracts of ripe, unripe and leaves of guava (psidium guajava); ripe, unripe and leaves of starfruit (Averrhoa carambola); ripe and unripe banana (Musa sapientum variety Montel); ripe and unripe papaya (Carica papaya); passionfruit (passiflora edulis F. Flavicarpa) peel; two varieties of Lansium domesticum peel (langsat and duku); rambutan (Nephelium lappaceum) peel and rambai (Baccaurea motleyana) peel were evaluated for antimicrobial activity against gram positive bacteria, gram negative bacteria, yeast and fungi (Staphylococcus aureus, Bacillus subtilis, Bacillus cereus, Lactobacillus bulgaricus; E. coli, Proteus vulgaricus, Pseudomonas aeruginosa, Salmonelli typhi; Saccharomyces cerevisiae, Candida lypolytica; Rhizopus spp., Aspergillus niger, and Chlamydomucor spp). The antimicrobial activities were tested using both the filter paper disc diffusion and tube dilution assays. Extracts from ripe starfruit, guava leaves and rambai peel showed strong activity against all the bacteria tested, in most cases with activity stronger than 50ug streptomycin. Passionfruit peel, ripe and unripe guava showed activity against all the bacteria tested except E. coli. Rambutan peel too showed activity against all the bacteria tested except towards Pseudomonas aeruginosa. Most of the fruit wastes showed some activity towards bacteria but poor activity against yeast or fungi. Extracts from bananas, papayas, passionfruit peel, Lansium domesticum peels and rambutan peels showed activity against Candida lypolytica while extractsfrom guava showed strong activity against Saccharomyces cerevisiae. Other than guava, ripe starfruit, rambai peel and rambutan peel showed potential for use against bacteria.